Avaliação de componentes do sistema renina- angiotensina circulantes em pacientes pediátricos portadores de leucemia aguda: revisão de literatura e estudo piloto - Ana Luísa Batista Pena (2022)
Introduction: Acute leukaemia are the most common cancer of childhood. In recent years there has been an important advance in the survival rate of these patients, attributed to a better understanding of the pathophysiology, genetic and molecular basis of the disease, as well as the establishment of protocols adapted to individual risk stratification of the disease. Despite its effectiveness, chemotherapy treatments are still associated with high toxicity, accounting for part of the morbidity and mortality of these patients. The emergence of new regimens and therapeutic strategies is essential for the treatment of those patients who, due to morbidity, cannot follow the treatment initially proposed or for those who have the disease in its most severe form, unresponsive to chemotherapy. There are a few studies in the literature relating the action of Renin Angiotensin System (RAS) molecules with the inhibition of growth and reduction of the proliferation of human cancer cells, as well as their action in accelerating bone marrow recovery by stimulating the proliferation of specific bone marrow progenitors. The objective of this study is to assess whether there is an association between the blood levels of RAS molecules in children with acute leukaemia and the form of presentation and evolution of the disease. Patients and Methods: This is a cross-sectional study carried out in a group of paediatric patients with acute leukaemia. The primary outcome of interest was the serum medullary and peripheral blood levels of Angiotensin II (Ang II) and Angiotensin-(1-7) [Ang-(1-7)] molecules. The study population consisted of paediatric patients with acute leukaemia followed-up at the Paediatric Haematology Service of Hospital das Clínicas, UFMG. The analysis of RAS biomarkers [Ang II, Ang-(1-7)] in samples from these patients was performed at the Interdisciplinary Laboratory for Medical Investigation of UFMG. In addition to the Ang-(1-7) and Ang II levels measured, the Ang-(1-7)/Ang II ratio was calculated as a parameter of the balance between the alternative and classical axes of the RAS. Results: Eleven patients with acute leukaemia and 20 healthy controls matched by sex and age were included. Blood levels of Ang II and Ang-(1-7) were measured in patients with acute leukaemia and healthy controls. Among the values found, it was observed that patients with acute leukaemia had significantly higher levels of both peptides when compared with healthy controls. However, no significant difference was found in the Ang-(1-7)/Ang II ratio between the two groups. A strong and positive correlation was detected between Ang II and Ang-(1-7) levels in patients with acute leukaemia. A similar result was not found in healthy controls. Among patients with acute leukaemia, no significant differences were observed in the levels of Ang II and Ang-(1-7) or in the Ang-(1-7)/Ang II ratio between samples of peripheral blood and medullary blood. Conclusion: The present study detected an important association between the presence of acute leukaemia and significantly higher levels of the peptides Angiotensin II and Angiotensin-(1-7). There was no significant difference between the levels of Ang II and Ang-(1-7), as well as the Ang-(1-7)/Ang II ratio, between the different levels of CNS involvement, different types of leukemia or in patients with hypercellularity at diagnosis.